Islamic Self-Moderation as a Spiritual Remedy for Fear of Missing Out in the Digital Age - Zainuddin Zainuddin; Mustafiyanti Mustafiyanti; Ulfa Hoyriah; Saskia Pungki; Nurdiana Sari; Muhammad Latif Nawawi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The development of digital technology has brought significant changes to the way humans interact, communicate, and access information. However, this advancement has also created new psychological challenges, such as the Fear of Missing Out a sense of anxiety arising from the fear of being left behind from others’ experiences. This phenomenon negatively affects mental health, social relationships, and spiritual balance. This article aims to analyze the concept of self-moderation in Islam as a spiritual solution to the Fear of Missing Out in the digital era. Using a qualitative phenomenological approach, this study examines relevant Qur’anic verses and Hadiths, interpreting Islamic principles applicable to managing digital behavior. The findings indicate that values such as qana‘ah (contentment), tawakkal (trust in God), and life balance form a spiritual foundation that helps individuals use social media proportionally. By practicing self-moderation, Muslims can avoid social anxiety and maintain harmony between worldly and spiritual needs